MUNTINGIA CALABURA SILVER NANOPARTICLES DETERIORATE OXIDATIVE IMPAIRMENT WITH POTENT ANTIBACTERIAL ACTIVITY - AHMED, SIDHRA SYED ZAMEER; KHADER, SYED ZAMEER AHMED; VALLIAMMAL, ELAYABARATHI MURUGESAN; ALI, SUNFIYA RAFEEK; SENTHILKUMAR, MOTHEES; VENKATACHALAM, MOHANAPRIYA; SARAVANAN, NILAVENDAN; SENTHILKUMARAN, DEEPTHY (International Journal of Applied Pharmaceutics, 2024)
Objective: The current study exemplifies the synthesis of silver nanoparticles using Muntingia calabura L. (Mc-AgNP’s) fruit extract utilizing a green approach and testing the efficacy of synthesized NP’s. Methods: The green synthesize approach was used to synthesis Mc-AgNP’s followed by characterization using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Energy Dispersive X-ray Spectroscopy (EDX), and Field Emission Scanning Electron Microscopy (FESEM). Radical scavenging activity was assessed using DPPH, FRAP, and H202, followed by antibacterial activity. Results: The characteristic features of synthesized Muntingia calabura silver nanoparticles (Mc-AgNP’s) were analyzed using FT-IR which particularizes different functional groups with a broadband at 3408 cm-1 representing hydroxyl (-OH) stretching a peak at 1593.27 cm-1 corresponds to C = O groups in amide whereas a dip at 1383 cm-1 represents C-N amine and C-O stretching of alcohol groups were found. The Crystallinity of synthesized Mc-AgNP’s exhibited face-centered cubic (fcc) crystalline structure and the bio-reduction of the silver ions in solution was monitored by Energy dispersive X-ray spectroscopy (EDX). The FESEM analysis indicates that Mc-AgNP’s were dispersed in the solution using micrographs and the size ranged from 10 to 60 nm. The synthesized Mc-AgNP’s efficiently scavenged free radicals in a dose-dependent manner with 69% for DPPH, 59.9% for FRAP, and 64% for H202 respectively. Further, the synthesized Mc-AgNP’s demonstrated a potent antimicrobial agent against tested bacterial and fungal strains with a maximum zone of inhibition observed in S. aureus, K. pneumonia, and P. vulgaris with 14.6, 13.8, and 12.4 mm. Similarly, antifungal activity with Trichoderma harzianum demonstrated the highest zone with 18 mm followed by Aspergillus oryzae with 7 mm. Conclusion: These results highlight the interesting potential of synthesized Mc-AgNP’s as an effective source of bioactive compounds with potent antioxidant and antibacterial activity.